2011
DOI: 10.1111/j.1364-3703.2011.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of the p23 silencing suppressor of Citrus tristeza virus differentially modifies viral accumulation and tropism in two transgenic woody hosts

Abstract: Citrus tristeza virus (CTV), a phloem-restricted closterovirus infecting citrus, encodes three different silencing suppressors (p25, p20 and p23), one of which (p23) is a pathogenicity determinant that induces aberrations resembling CTV symptoms when expressed ectopically in transgenic citrus hosts. In this article, the effect of p23 ectopic expression on virus infection was examined in sweet orange (SwO), a highly susceptible host, and sour orange (SO), which severely restricts CTV cell-to-cell movement. Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…In this context, it is worth pointing out that the ectopic expression of RSSs enhances the accumulation of some viruses (28)(29)(30), most likely by suppressing the host antiviral RNA silencing. Consistent with this view, CTV also accumulates when p23 is ectopically expressed in sour orange (27). In contrast, expression of some RSSs has no effect on viroid accumulation in PSTVd-infected N. benthamiana (17).…”
supporting
confidence: 57%
See 3 more Smart Citations
“…In this context, it is worth pointing out that the ectopic expression of RSSs enhances the accumulation of some viruses (28)(29)(30), most likely by suppressing the host antiviral RNA silencing. Consistent with this view, CTV also accumulates when p23 is ectopically expressed in sour orange (27). In contrast, expression of some RSSs has no effect on viroid accumulation in PSTVd-infected N. benthamiana (17).…”
supporting
confidence: 57%
“…Sequencing of RT-PCR amplicons from CDVd-infected plants indicated that the CDVd used as inoculum remained stable in all the treatments. The presence of p23, p20, and p25 was confirmed in equalized protein extracts of the transgenic lines, as well as in singly infected and coinfected nontransformed controls, by SDS-PAGE and Western blot analysis with p23 and p20 antisera (27) (Twentyfirst Century Biochemicals, Inc.) and with a mixture of 3DF1 and 3CA5 antibodies for detecting p25 (data not shown). Northern blot hybridization only detected the CDVd-sRNAs in transgenic lines expressing p23 (Fig.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…It should be noted that viroid titres in the leaf blades of C. karna, sour orange and trifoliate orange were rather low, suggesting that viroids were only present in the secondary veins -from where they were unable to exit and invade other cell types, including mesophyll cells -thus explaining why they could not be detected in protoplasts. Phloem-restricted infection is not exceptional in citrus and has been reported for viruses, like citrus tristeza virus (Fagoaga et al, 2011). The mature phloem contains the sieve tube, composed of a vertical column of elongated cells devoid of nuclei that are responsible for the longdistance movement of viruses and viroids, and companion cells with nuclei competent for virus and viroid replication.…”
mentioning
confidence: 99%